Synthesis of single-stranded RNA marker / Abdul Shukor Said - Said, Abdul Shukor (2009)
Single-stranded RNA marker is widely used in biotechnology field. Producing it on our own will reduce the laboratory cost. This study aimed to synthesis single-stranded RNA marker. In this research, two method were used which are PCR process and followed by in vitro transcription. PCR is a special technique to amplify the DNA sequence of interest. A successful laboratory testing for PCR depends on sensitivity and specificity of PCR method itself. In vitro transcription is a technique to transcribe double stranded DNA to single stranded RNA. Ten different size of DNA ranging from 1 kb to 10 kb were amplified and undergo in vitro transcription to synthesis single stranded RNA with the same bases range.